Experience of the first 50 cases of cordocentesis after training with model - Fuanglada Tongprasert (2018)
Objective: To describe the experience of the first 50 cases of cordocentesis after practicing with cordocentesis model. Material and Method: Cordocentesis model consisted of a water-filled transparent glass box covered with a rubber latex sheet with or without piece of pork skin. A 30-cm umbilical cord filled with mercurochrome, hung inside the container, was the target for the puncture. As in real practice, the trainee had to try to aspirate the red mercurochrome from the umbilical cord using a spinal needle under ultrasonographic guidance. After practicing with the model for 300 procedures, the trainee was allowed to perform cordocentesis on pregnant women at gestational age of 18-22 weeks by herself under expert supervision with time limit of 30 minutes. The procedure not successful in 30 minutes was considered failure. Duration of procedures, placental site, puncture site, and related complications were recorded for subsequent analysis. Results: After practicing with model for 300 procedures, real cordocentesis was performed by the trainee on 50 pregnant women. The success rate in obtaining fetal blood within 30 minutes was 100%. Most of them (92%) took less than 10 minutes to complete the procedure. Puncture site bleeding and fetal bradycardia were the most common immediate complications, found in 30% and 8% respectively, and spontaneously resolved within few minutes. Conclusion: Without any fetal and maternal jeopardy, cordocentesis model is simple, inexpensive but highly effective for the beginner to gain their experience, skill and prepare themselves for cordocentesis with confidence. However, the reduction of fetal loss rate with the training program remains to be further tested.